Correlation Between Age at Menarche and Breast Cancer Incidence in Dr. Cipto Mangunkusumo National General Hospital, Jakarta, Indonesia (2010-2014) - Zuraidah, Endah; Agatha, Nur Fitrianingsih Pujiano; Qanita Edwar, Sarah; Irianti Handayani, Supri (Asian Pacific Journal of Cancer Care, 2023)
Background and objective: Breast cancer is one of the most prevalent malignancies among Indonesian women. Numerous risk factors can increase the likelihood of developing breast cancer, and hormonal factors appear to play a significant role in many cases. This research aimed to determine the relationship between age at menarche and breast cancer incidence in Dr. Cipto Mangunkusumo National General Hospital, Jakarta, Indonesia, from 2010 to 2014. Materials and Methods: This retrospective cross-sectional study utilized a random sampling technique with a sample size of 98 participants. Data were collected from the Archive Unit of Anatomical Pathology of the Faculty of Medicine, University of Indonesia (FMUI), with further investigation in the Medical Record Unit and Medical Department of Surgery at Dr. Cipto Mangunkusumo National General Hospital, Jakarta. Data analysis was performed using the chi-square test and Fisher’s exact test. Results: There was no statistically significant association between age at menarche and breast cancer incidence at Dr. Cipto Mangunkusumo National General Hospital, Jakarta, during the study period (p > 0.05). The results also indicated that the 40-49 year age group had the highest number of breast cancer cases compared to other age groups. Furthermore, an age at first menstruation of over 12 years was associated with the highest frequency of breast cancer cases in the study population. Conclusion: The age at first menstruation did not statistically significantly affect breast cancer incidence at Dr. Cipto Mangunkusumo Hospital, Jakarta, during the period of 2010-2014. However, further research utilizing different study designs and larger sample sizes is recommended.